ChemInform Abstract: Synthesis of Fluorinated and Trifluoromethyl‐Substituted Alkenes Through the Modified Julia Olefination: An Update. Issue 31 (August 2015) - Pfund, Emmanuel; Lequeux, Thierry; Gueyrard, David
Abstract Review: [36 refs.